2017
DOI: 10.1016/j.drugalcdep.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and virological failure among HIV-infected people who inject drugs on antiretroviral treatment in China: An observational cohort study

Abstract: For HIV-infected PWID receiving ART, engagement in MMT and discontinuation of drug use were more likely to be associated with lower mortality and virological failure compared with active drug use. In order to maximize the clinical impact of ART, HIV treatment programs in China should be further integrated with MMT and social services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…It is possible that PWID receiving and not receiving MMT may have different characteristics, and that the effect of MMT on adherence may be mitigated over time [19]. Another study in China found that those engaged in MMT had substantially lower mortality rate than those who actively use drugs, while virological failure rate were similar between the two groups [29]. In our study, anecdotal information suggested that there is an increasing use of amphetamine-like stimulants among people who inject heroin and MMT users, which might have had impact on the adherence and viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that PWID receiving and not receiving MMT may have different characteristics, and that the effect of MMT on adherence may be mitigated over time [19]. Another study in China found that those engaged in MMT had substantially lower mortality rate than those who actively use drugs, while virological failure rate were similar between the two groups [29]. In our study, anecdotal information suggested that there is an increasing use of amphetamine-like stimulants among people who inject heroin and MMT users, which might have had impact on the adherence and viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…This study reports that HIV drug-experienced individuals in formal or informal employment were protected from VF. Unemployment among HIV-infected individuals was previously described as a stressful event which reduced adherence to prescribed HIV medications resulting in high rates of VF [ 35 ] and increased mortality [ 36 ]. Supporting and engaging PLHIV in income-generating activities may stabilize financial and social status and positively impact drug adherence and favourable treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 124, 63 (50.8%) participants had VF and 61 (49.2%) had VS. The age of the 124 participants ranged from 15 to 79 years, with a median [IQR] age of 45 [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] years. Of the 124; 82 (66.1%) were females and 89 (71.8%) were employed in either formal or informal sector.…”
Section: Demographic Characteristics Of Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that males less frequently visit health care providers for health concerns and in HIV-infected patients this results in prolonged elevated viral load levels before intervention and episodes of ART interruption in those already receiving treatment. One recent study highlighted this devastating association and found that HIV-infected individuals who were active IVDUs experience higher mortality rates due to poor viral management and ART interruption [77]. Nevertheless, the analysis of the Cardiovascular Diseases in HIV-infected Subjects (HIV-HEART) study by Reinsch et al [39], the multivariate analysis of an HIV-infected cohort in Spain by Quezada et al [13] and the study by Schwarze-Zander et al [73] report greater predominance of HIV-infected females with PAH.…”
Section: Epidemiology Of Pah In Hiv-infected and Intravenous Drug Usersmentioning
confidence: 99%